Cruzain inhibition by hydroxymethylnitrofurazone and nitrofurazone: investigation of a new target in Trypanosoma cruzi - Trossini, Gustavo H. G.; Malvezzi, Alberto; T-do Amaral, Antonia; Rangel-Yagui, Carlota Oliveira; Izidoro, Mario A.; Cezari, Maria Helena S.; Juliano, Luiz; Chin, Chung Man [UNESP]; Menezes, Carla M. S.; Ferreira, Elizabeth Igne (Taylor & Francis Ltd, 2010)
Nitrofurazone (NF) and its derivative, hydroxymethylnitrofurazone (NFOH), have presented antichagasic activity. NFOH has higher activity and lower mutagenicity. The aim of this work was to assess whether NF and its derivative NFOH would also be inhibitors of cruzain, besides their trypanothione reductase inhibitory activity. In vitro cruzain inhibition tests were performed for both compounds, and the 50% inhibitory concentration (IC(50)) for NF and NFOH presented values of 22.83 +/- 1.2 mu M and 10.55 +/- 0.81 mu M, respectively. AM1 semi-empirical molecular modeling studies were performed to understand the activity of the compounds, corroborating the observed cruzain inhibitory activity.
Keywords: Chagas'; disease; cruzain inhibitory activity; molecular modeling; nitrofurazone derivative; Trypanosoma cruzi